2016
DOI: 10.3171/2015.10.jns151516
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative pregabalin for reducing pain, analgesic consumption, and anxiety and enhancing sleep quality in elective neurosurgical patients: a prospective, randomized, double-blind, and controlled clinical study

Abstract: OBJECTIVE The aim of this study was to assess in-hospital (immediate) postoperative pain scores and analgesic consumption (primary goals) and preoperative anxiety and sleep quality (secondary goals) in patients who underwent craniotomy and were treated with pregabalin (PGL). Whenever possible, out-of-hospital pain scores and analgesics usage data were obtained as well. METHODS This prospective, randomized, double-blind and controlled study was conducted in consenting patients who underwent elective craniotomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 48 publications
2
57
0
1
Order By: Relevance
“…In a cohort of patients undergoing total knee replacement, a strong correlation between sleep quality as assessed with polysomnography and postoperative active range of motion was reported (Gong et al., ). In another cohort of neurosurgical patients, preoperative pregabalin significantly improved preoperative sleep quality and also reduced postoperative pain intensity, although in this study, pregabalin may have had a direct analgesic effect (Shimony et al., ).…”
Section: Discussionmentioning
confidence: 58%
“…In a cohort of patients undergoing total knee replacement, a strong correlation between sleep quality as assessed with polysomnography and postoperative active range of motion was reported (Gong et al., ). In another cohort of neurosurgical patients, preoperative pregabalin significantly improved preoperative sleep quality and also reduced postoperative pain intensity, although in this study, pregabalin may have had a direct analgesic effect (Shimony et al., ).…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, the action of antidepressants has been reported to reduce anxiety and sleep quality in surgical patients, as well as to reduce pain and analgesic consumption (22). Identification and reduction of psychological factors can also help to optimize pain management in thoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, administration of pregabalin 150 mg on the evening before surgery, as premedication 2 hours before surgery, and twice per day for 72 hours after craniotomy improved pain scores and reduced analgesic consumption during hospitalization, an effect extended to 3 months after surgery. Furthermore, administration of pregabalin was related to fewer side effects, such as PONV, anxiety, and sleep disorders up to hospital discharge …”
Section: Resultsmentioning
confidence: 96%
“…Presumably, the failure to identify any clear positive effect of premedication with 600 mg of gabapentin on postcraniotomy pain relief and opioid consumption during the 18‐hour follow‐up period was due to inadequate dosing, as it has been shown that a dose of 1,200 mg/day might be needed for successful analgesic effect following craniotomy . However, preemptive administration of 150 mg pregabalin and twice‐daily dosing for 3 days following craniotomy optimally affected antinociception and the occurrence of adverse effects during the first 48 hours after craniotomy . Considering that the clinical effects of gabapentinoids are not solely pharmacologically modulated but may also depend upon the activities of unidentified neurological pathways, such as pain neuroadaptation, more studies are warranted to elucidate their potential role in the neurosurgical setting, both on a short‐term and long‐term basis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation